Problems of land reform implementation in Thailand : land sale to farmers under the land reform programme in private land - Eathipol Srisawaluck; Weber, Karl E.; Demaine, Harvey; Suvit Yodmani; Gonzales, Jr. R. L.; Agricultura l Land Reform Office, Ministry of Agriculture and Cooperatives Roya l Thai Government (Bangkok : Asian Institute of Technology, 1988)
The major objective of agricultural land reform in Thailand is to solve the problem of tenancy and landlessness through acquiring land suitable for agriculture from absentee landlords, or through allocating public land to farmers in need, either on a rental or on a hire-purchase basis. Providing land ownership to each farmer is the ultimate purpose of land reform. After several years of land reform implementation it became evident that its goal could hardly ever be realized, because only a minority of tenant farmers in the land reform area had been interested in hire-purchasing the land they till. Moreover, some of those farmers who had erstwhile hire-purchased land renounced their hire-purchasing contracts later-on. This study found out that the major reasons stated by both tenants and renouncers for rejecting or for renouncing hire-purchasing contracts included sizes of land allocated being too small for earning a livelihood, poor soil and implicit low productivity, and consequently low income as well as indebtedness. This failure was also due to the fact that land allocated by the Agricultural Land Reform Office (ALRO) to farmer5 was identical with plots that farmers had rented from private landowners until the time of land reform implementation. Some of these old tenants had never paid any rent to the former landowners for extended periods, owing to constraints imposed by nature or sheer deliberate evasion of payment. These farmers found it difficult to enter into any type of formal contract that would oblige them to make regular payments. In the absence of any adequate infrastructure development, without any sound measure of financial assistance, and lacking any suitable models of farm management, farmers who had switched from tenant to landowner status under the ALRO strategy for creating land ownership through hire-purchasing had ;.iot experienced any tangible change of their socio-economic condition. The study includes specific recommendations for measures to promote the acceptance and adoption of hire-purchasing and for strengthening farmers' ability to generate higher income from their own land in the long run.
A Thesis Submitted in Partial Fulfilment of the Requirements for t he Award of the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Land reform -- Thailand